2021
DOI: 10.1590/s1984-29612021090
|View full text |Cite
|
Sign up to set email alerts
|

Community and infracommunities of metazoan parasites in Hemiodus unimaculatus (Hemiodontidae) from Jari River basin, a tributary of Amazon River (Brazil)

Abstract: Parasites are an important part of biodiversity, and knowledge of species and their relationship with their hosts helps in monitoring an ecosystem over time. The aim of this study was to investigate the fauna of metazoan parasites in Hemiodus unimaculatus from the Jari River, in the eastern Amazon region, northern Brazil. Of the fish examined, 96.7% were parasitized by one or more species, and a total of 336 parasites such as Dactylogyridae gen. sp.1, Dactylogyridae gen. sp.2, Dactylogyridae gen. sp.3, Dactylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Mites presented low levels of infection in the gills of E. pisonis in the Amazon River, but have been widely found on a variety of vertebrates, including fish and piscivorous birds (Lizama et al, 2013). In Amazonian fish, mite infection has been reported in Colossoma macropomum Cuvier, 1816 (Gonçalves et al, 2018), Brachyplatystoma vaillantii Valenciennes, 1840(Brito-Junior & Tavares-Dias, 2021 and Hemiodus unimaculatus Bloch, 1794 (Almeida et al, 2021).…”
Section: Component Communities Of Metazoan Parasitesmentioning
confidence: 99%
“…Mites presented low levels of infection in the gills of E. pisonis in the Amazon River, but have been widely found on a variety of vertebrates, including fish and piscivorous birds (Lizama et al, 2013). In Amazonian fish, mite infection has been reported in Colossoma macropomum Cuvier, 1816 (Gonçalves et al, 2018), Brachyplatystoma vaillantii Valenciennes, 1840(Brito-Junior & Tavares-Dias, 2021 and Hemiodus unimaculatus Bloch, 1794 (Almeida et al, 2021).…”
Section: Component Communities Of Metazoan Parasitesmentioning
confidence: 99%
“…2020). Almeida et al (2021) confirmed the first record of Urocleidoides for the gills of Hemiodus unimaculatus (Bloch 1794) in the Jari River, a tributary of the Amazon River; however, there has been no description of a species of Urocleidoides for this family of fish.…”
Section: Introductionmentioning
confidence: 95%
“…Fifty-two species of Urocleidoides are considered valid to date and occur especially in Neotropical Characiform fishes (Ferreira et al 2018;Oliveira et al 2020;Zago et al 2020;De Oliveira et al 2021;Santos Neto and Domingues 2023), especially in hosts from the Anostomidae and Erythrinidae (Zago et al 2020). Almeida et al (2021) confirmed the first record of Urocleidoides for the gills of Hemiodus unimaculatus (Bloch 1794) in the Jari River, a tributary of the Amazon River; however, there has been no description of a species of Urocleidoides for this family of fish.…”
Section: Introductionmentioning
confidence: 99%